An indicator set to track resilience to climate change in agriculture: A policy-maker's perspective. (March 2019) - Bizikova, Livia; Larkin, Patricia; Mitchell, Scott; Waldick, Ruth
Abstract: Resilience-based approaches to climate change have yet to be widely applied in agriculture. In this sector, indicators have been centered on the impacts of climate on production systems, crops, yields, infrastructure, financial performance, farmers' livelihoods and food security. This paper focuses on designing an indicator set to capture the resilience of agriculture to inform decision-making frameworks and policies. The indicators' selection and definition were driven by their relevance for decision-making through the combined knowledge of policy and information priorities on climate change impacts and vulnerabilities as well as pragmatic issues relating to data availability. In total, 36 indicators were selected covering the following areas: regional drivers of the change to the agricultural sector (demographics, agricultural markets, climate); farmland production activities (food and feed); non-farm economy; and primary outcomes (off-farm net income, numerous environmental services). By coordinating this process among policy-makers with different roles in regional planning, we were able to identify shared information needs among the various sectoral representatives. The indicator selection process also captured policy gaps potential responses that could increase resilience and feed directly into policy reviews, thereby strengthening integration of actions across sectors. This indicator set emphasizes that the relationships between government agencies and both industry and academia may be improved by addressing gaps in data availability, accessibility, and privacy constraints.